1999
DOI: 10.1038/sj.bjp.0702550
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect with Phe‐Gly‐Leu‐Met‐NH2 of the C‐terminal of substance P and insulin‐like growth factor‐1 on epithelial wound healing of rabbit cornea

Abstract: 1 We previously reported that substance P and insulin-like growth factor-1 (IGF-1) synergistically stimulate corneal epithelial wound healing in vitro and in vivo. We wished to identify which portion of the amino acid sequence of substance P might be responsible for this synergism. 2 Corneal epithelial migration was not a ected by the addition of any one of the following factors: substance P; Phe-Gly-Leu-Met-NH 2 (C-terminal of substance P); Val-Gly-Leu-Met-NH 2 (C-terminal of neurokinin A, neurokinin B, and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 45 publications
1
38
1
Order By: Relevance
“…Although previous studies have confirmed that SP enhances corneal epithelial migration when combined with IGF-1 or EGF (41,44,45), the exact mechanism remains unclear. Here we show that SP reactivates Akt, EGFR, and Sirt1 and promotes ROS scavenging capacity that are impaired by hyperglycemia.…”
Section: Discussionmentioning
confidence: 86%
“…Although previous studies have confirmed that SP enhances corneal epithelial migration when combined with IGF-1 or EGF (41,44,45), the exact mechanism remains unclear. Here we show that SP reactivates Akt, EGFR, and Sirt1 and promotes ROS scavenging capacity that are impaired by hyperglycemia.…”
Section: Discussionmentioning
confidence: 86%
“…Although SP is a potent positive regulator of cell proliferation, SP activity has also been correlated with cell attachment and migration, and, more loosely, with cellular differentiation. SP, in synergy with insulin-like growth factor-1, has been shown to induce rabbit corneal epithelial cell attachment to fibronectin matrix, promote subsequent migration, and increase levels of the integrins ␣ 5 and ␤ 1 mRNA (50,51). Furthermore, SP has been implicated in angiogenesis by inducing the formation of capillary-like structures from endothelial cells placed on a Matrigel matrix (52).…”
Section: Discussionmentioning
confidence: 99%
“…10 The four-amino-acid sequence at the carboxyl terminus of substance P (phenylalanineglycine-leucine-methionine amide, or FGLM-amide) mimics the synergistic effects of the full-length molecule with IGF-1 on the corneal epithelium. 11 Moreover, we applied eye drops containing FGLM-amide and IGF-1 to treat successfully a case of neurotrophic keratopathy. 12 We have now evaluated in an open trial the clinical effi cacy of eye drops containing this combination of agents in the treatment of persistent epithelial defects in individuals with neurotrophic keratopathy.…”
mentioning
confidence: 99%